Emotional State of Being Moved Elicited by Films: A Comparison With Several Positive Emotions - Kimura, Kenta; Haramizu, Satoshi; Sanada, Kazue; Oshida, Akiko (Frontiers in Psychology, 2019)
This study investigated the facial and physiological activities that are associated with the emotional state of being moved. We elicited the emotional states of being moved, amusement, attachment, and calmness by presenting participants with film clips; we assessed their electromyographic, electrodermal, and cardiac responses to the films. Further, we used a high- and low-arousal moving film to examine the effect of different levels of arousal on facial and physiological responses to moving films. We compared facial and physiological responses to positive-emotion and emotionally neutral films. Analysis of subjective emotion scale ratings revealed that the films had successfully elicited the target positive emotions and that the high- and low-arousal moving films had elicited the feeling of being moved in accordance with the anticipated level of intensity. In comparison to the other types of positive-emotion films, the two moving films resulted in an increase in corrugator electromyography activity and skin conductance responses, which in turn were modulated by the arousal level of the moving films. However, cardiac measures such as heart rate did not differ across the different film conditions. These results suggest that film clips can elicit different intensities of the emotional state of being moved and that facial muscle and electrodermal activities but not cardiac activity characterize the film-induced emotional state of being moved.